Liver iron modulates hepcidin expression during chronically elevated erythropoiesis in mice. Issue 6 (21st October 2013) - Díaz, Víctor; Gammella, Elena; Recalcati, Stefania; Santambrogio, Paolo; Naldi, Arianne Monge; Vogel, Johannes; Gassmann, Max; Cairo, Gaetano
<x xml:space="preserve">Abstract</x> The liver‐derived peptide hepcidin controls the balance between iron demand and iron supply. By inhibiting the iron export activity of ferroportin, hepcidin modulates iron absorption and delivery from the body's stores. The regulation of hepcidin, however, is not completely understood and includes a variety of different signals. We studied iron metabolism and hepcidin expression in mice constitutively overexpressing erythropoietin (Epo) (Tg6 mice), which leads to excessive erythropoiesis. We observed a very strong down‐regulation of hepcidin in Tg6 mice that was accompanied by a strong increase in duodenal expression of ferroportin and divalent metal tranporter‐1, as well as enhanced duodenal iron absorption. Despite these compensatory mechanisms, Tg6 mice displayed marked circulating iron deficiency and low levels of iron in liver, spleen, and muscle. To elucidate the primary signal affecting hepcidin expression during chronically elevated erythropoiesis, we increased iron availability by either providing iron (thus further increasing the hematocrit) or reducing erythropoiesis‐dependent iron consumption by means of splenectomy. Both treatments increased liver iron and up‐regulated hepcidin expression and the BMP6/SMAD pathway despite continuously high plasma Epo levels and sustained erythropoiesis. This suggests that hepcidin expression is not controlled by erythropoietic signals directly in this setting. Rather, these results indicate that iron consumption for erythropoiesis modulates liver iron content, and ultimately BMP6 and hepcidin. Analysis of the BMP6/SMAD pathway targets showed that inhibitor of DNA binding 1 (ID1) and SMAD7, but not transmembrane serine protease 6 (TMPRSS6), were up‐regulated by increased iron availability and thus may be involved in setting the upper limit of hepcidin. Conclusion: We provide evidence that under conditions of excessive and effective erythropoiesis, liver iron regulates hepcidin expression through the BMP6/SMAD pathway. (Hepatology 2013; 58:2122–2132)